A re-investigation of the mycolic acids of Mycobacterium avium. (August 2020) - Jones, Alison; Lee, Oona Y-C.; Minnikin, David E.; Baird, Mark S.; Al Dulayymi, Juma'a R.
Graphical abstract: The isolation of the complete wax ester fraction of M. avium is described for the first time, including the trans -cyclopropane A as a major component. The mixture of minor trans- alkene wax diacids included the isomer B in which the methyl-substituent is on the distal carbon adjacent to the alkene. Highlights: The in-tact wax ester fraction of M. avium is isolated for the first time, including a trans -cyclopropane with a distal methyl substituent as a major component. The components correlate well with those partially reported earlier. The mixtures of wax esters or of the corresponding wax diacids each contained minor amounts of a trans -alkene previously believed to have a methyl-substituent on the adjacent carbon proximal to the hydroxy-acid. In both cases, it is now shown that the isomer in which the methyl-substituent is on the distal carbon adjacent to the alkene is also present. In the case of the wax-diacid, this was the major isomer. This isomer relates directly to the major trans -cyclopropane wax ester, and its isolation may be of value in analysing the rates of biochemical leading to different mycolic acids and wax esters. Abstract: Mycolic acid methyl esters were extracted from Mycobacterium avium by a mild saponification protocol, designed to preserve labile components. The resulting mixture of α-, keto- and wax ester mycolates was accompanied by some degraded ω-carboxymycolic acid dimethyl esters, whose overall structures were found to support previous studies. Chromatography of the mono-carboxylic mycolates gave an inseparable mixture of keto- and wax ester mycolates and separate α-mycolates. Reduction of the ketomycolate components allowed isolation and characterisation of intact wax ester mycolates for the first time. Minor α- and ω-carboxymycolates were detected in which methyl branches were located on either the proximal or distal sides of trans -alkene groups.